2011
DOI: 10.1007/s10897-010-9341-x
|View full text |Cite
|
Sign up to set email alerts
|

Peer Observed Interaction and Structured Evaluation (POISE): A Canadian Experience with Peer Supervision for Genetic Counselors

Abstract: Peer observation, while often used in other professions, has not been formally applied in genetic counseling. The objective of this study was to pilot a method of peer evaluation whereby genetic counselors observed, and were observed by, each other during patient interaction. All of the available genetic counselors participated in both rounds of the pilot study (six in round one, seven in round two). The genetic counselors that observed the session used an observation room. Most participants reported learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…The short time interval between the session and the feedback/supervision meeting was seen by participants as important in avoiding loss of important details. This concurs with findings from other studies (Goldsmith et al 2011). This minimises the biases with time as individuals' inner narratives interpret and re-interpret the experience of the session (Kessler 2007).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The short time interval between the session and the feedback/supervision meeting was seen by participants as important in avoiding loss of important details. This concurs with findings from other studies (Goldsmith et al 2011). This minimises the biases with time as individuals' inner narratives interpret and re-interpret the experience of the session (Kessler 2007).…”
Section: Discussionsupporting
confidence: 90%
“…In the context of training genetic counseling students, live supervision has been acknowledged as an effective method of promoting skill development and professional development for both students and supervisors (Hendrickson et al 2002). Goldsmith et al (2011) piloted a method of "peer observed interaction and structured evaluation" (POISE) whereby genetic counselors observed, and were observed by each other during patient appointments. Advantages of the POISE model included a reduction in recall bias, and an increased opportunity for concrete feedback regarding patient interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many participants cited informal and formal peer supervision as effective in their supervision skill development. Peer supervision thus comprises a promising method for supervisor training; it has been shown to enhance professional development as it promotes self-reflective practice and models alternative approaches (Goldsmith et al 2011;Sexton et al 2013;Zahm et al 2008).…”
Section: Training Implicationsmentioning
confidence: 99%
“…Live supervision is the most common supervision modality in genetic counseling training programs, followed by review of student self-reported descriptions of the session (Lindh et al 2003;Masunga et al 2014). These are the dominant methods of supervision in genetic counseling, as less than 10 % of one sample of supervisors reported using audio or visual recording or remote supervision (Masunga et al 2014), though peer supervision has been explored in the U.S. (Zahm et al 2008), Canada (Goldsmith et al 2011), and Australia (Sexton et al 2013). Given the added pressure of having a supervisor present on top of already being evaluated, the present study sought to investigate potential differences in the way supervisees perceive supervision across different levels of anxiety.…”
mentioning
confidence: 99%